From Patient Navigation to Cancer Justice: Toward a Culture-Centered, Community-Owned Intervention Addressing Disparities in Cancer Prevention - Sastry, Shaunak; Zoller, Heather M.; Walker, Taylor; Sunderland, Steve (Frontiers in Communication, 2017)
In this study, we analyze data from an ongoing academic–community collaboration targeted at conceptualization and delivery of a patient navigation intervention for cancer prevention. Echoing overall United States trends, the region under study is earmarked by significant socioeconomic and racial disparities in cancer outcomes. While there is a large body of research on the use of patient navigation across the continuum of cancer care, the role of communication in shaping navigation is unclear in the literature. Responding to this gap, we use the culture-centered approach to document how community-based “lay” patient navigators’ local knowledge and cultural expertise shaped the scope and meanings of patient navigation for a predominantly African-American population. Qualitative data in the form of navigator interviews, participant observation of navigation, and research team members’ reflexive journals were used to document how the definition and scope of navigation were re-inscribed by community navigators. While navigation was initially equated with screening promotion, interaction with community members led to the development of more listening-focused and structural barrier-focused conceptualization of patient navigation. Finally, we discuss the implications and contributions and limitations of this study.